"Metempsychosis" and "Marvelous Affinities": Re-Imagining the Past in the Ilyāḏah by Sulaymān al-Bustānī (1904) and in the Divano di ʿOmar ben al-Fared by Pietro Valerga (1874) - Benigni, Elisabetta (Oriente moderno, 2021)
This article focuses on the image of the past in two translations produced in the contexts of the Arab Nahḍah and of the Italian Risorgimento. The first translation is the Italian rendering of ʿOmar ibn al-Fāriḍ’s mystical poems, published in 1872 by Pietro Valerga (1821-1903). The second is the Arabic translation of the Iliad, published in 1902 by Sulaymān al-Bustānī (1856-1925). Both translators refer to the past as a translation strategy: Pietro Valerga reads Ibn al-Fāriḍ through the verses of Petrarch and, in his work’s introduction, emphasizes the transmission of medieval Arab poetry to Italy; Sulaymān al-Bustānī reconstructs the world of the Iliad through Arabic poetic tradition and compares Greece to the ǧāhiliyyah (pre-Islamic age). The article sheds light on the potential of translation as a space of re-imagination of the past and invites us to read the works as two distinct, yet akin, attempts to express original interpretations of Italian and Arabic literary histories based on syncretism and cross-cultural translatability.